2019
DOI: 10.1074/jbc.ra119.007601
|View full text |Cite
|
Sign up to set email alerts
|

In vivo stabilization of OPA1 in hepatocytes potentiates mitochondrial respiration and gluconeogenesis in a prohibitin-dependent way

Abstract: Edited by Jeffrey E. Pessin Patients with fatty liver diseases present altered mitochondrial morphology and impaired metabolic function. Mitochondrial dynamics and related cell function require the uncleaved form of the dynamin-like GTPase OPA1. Stabilization of OPA1 might then confer a protective mechanism against stress-induced tissue damages. To study the putative role of hepatic mitochondrial morphology in a sick liver, we expressed a cleavage-resistant long form of OPA1 (L-OPA1⌬) in the liver of a mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 64 publications
(86 reference statements)
0
38
1
Order By: Relevance
“…Loss of Phb2 in Caenorhabditis elegans and mice leads to embryonic lethality 24,25 . Several tissue specific Phb2 knockout mice have been used to explore its functions in physiological and pathological processes [26][27][28][29] . In forebrainspecific PHB2-deficient mice, tau hyper-phosphorylation and neurodegeneration were observed 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of Phb2 in Caenorhabditis elegans and mice leads to embryonic lethality 24,25 . Several tissue specific Phb2 knockout mice have been used to explore its functions in physiological and pathological processes [26][27][28][29] . In forebrainspecific PHB2-deficient mice, tau hyper-phosphorylation and neurodegeneration were observed 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of PHB2 in podocytes led to the development of glomerulosclerosis due to PHB2's extramitochondria role in the assembly of the slit diaphragm protein-lipid supercomplex 27 . Hepatocyte-specific Phb2 knockout mice exhibited liver failure and impaired gluconeogenesis 26 . The above studies demonstrate that PHB2 is essential for maintaining normal organ function.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (1) showed that in vivo deletion of prohibitin-2 (Phb2) in hepatocytes (Hep-Phb2 Ϫ/Ϫ ) leads to impaired gluconeogenesis, reduced food intake, severe hypoglycemia, and, subsequently, poor survival. Phb2 and its homologous protein Phb1 form heterodimers in the mitochondria and are functionally interdependent (1)(2)(3). Consequently, the knockdown of either member leads to a parallel loss of the other member (1-4).…”
mentioning
confidence: 99%
“…Similar to the Hep-Phb2 Ϫ/Ϫ mice, the Hep-Phb1 Ϫ/Ϫ mice display a parallel reduction in the levels of heterodimeric partners in hepatocytes and decreased body weight (1, 4). However, the major liver-specific phenotypes of the Hep-Phb1 Ϫ/Ϫ mice and the Hep-Phb2 Ϫ/Ϫ mice are largely different, with distinctions like increased liver weight and the development of hepatocellular carcinoma in the former and reduced liver weight and severe hypoglycemia in the latter (1,4). Most importantly, the Hep-Phb1 Ϫ/Ϫ mice survive much longer than the Hep-Phb2 Ϫ/Ϫ mice (1, 4) and other, cell type-specific knockout mouse models of Phb2 (2, 3).…”
mentioning
confidence: 99%
See 1 more Smart Citation